ANALISIS VARIABEL NIAT MENGADOPSI MOBILE BANKING PADA BANK SYARIAH - Jatnika, Muhammad Dzulfaqori; Friantoro, Dian; Andani, Listia; Mutmainah, Lu'liyatul (I-Economics, 2022)
The purpose of this study is to analyze the factors that influence the intention to adopt mobile banking in the Gerbangkertosusila Region. This type of research is a quantitative study using the population of the Gerbangkertosusila Region as a population. While the sample used was 385 respondents with a non-probability sampling method. Primary data obtained by distributing questionnaires online. Data analysis technique in this research is Partial Least Squares-Structural Equation Model (PLS-SEM). The findings in this study indicate that the variable perceived benefits, perceived easy to use, perceived risk, attitudes, and social influence significantly influence the intention to adopt mobile banking. Variable perceptions of usefulness, perceptions of convenience, attitudes, and social influence have a positive relationship while risk perception has a negative relationship with the intention to adopt mobile banking in the Gerbangkertosusila Region. This finding is expected to make Islamic banking policy makers understand the problem of intention to adopt mobile banking faced by their customers. This information will be useful in developing new policies or strategies to maximize the potential of mobile banking users in Indonesia, especially in the Gerbangkertosusila Region.